Coffee, mycotoxins and climate change - Paterson, R. R. M. (2014)
Coffee is very valuable.However, it is subjected to various pest and diseases ofwhichmycotoxin contamination is of great importance in terms of the health of consumers and economic loss. The major compound of concern is ochratoxin A (OTA) which has statutory limits imposed on the commodity in, for example, the European Union. The concentrations of OTA appear often well within the limits and the situation is containable, although some surveys revealed levels higher than statutory limits and frequency of contamination was often high. The producing fungi are Aspergilli. Nevertheless, there remains some misidentification in the literature in relation to Aspergillus ochraceus and Aspergillus westerdijkiae: other important producers are Aspergillus carbonarius and Aspergillus niger. Coffee husks are high in OTA and are fortunately removed during processing. Beans obtained after falling on the soil and coffee which had been floated as part of processing, were reported as high in OTA and should be avoided. The presence of aflatoxins (AF) needs consideration.More work is required on the presence of fumonisins in coffee. The effect of climate change on mycotoxins in coffee requires urgent consideration as, for example, AF may become more problematic than OTA in 50 years. Finally, careful monitoring of coffee is essential to nurture this desirable commodity into the future.